Aping the Ape: Kafka's "Report to an Academy" - Ziad Elmarsafy (Studies in 20th & 21st Century Literature, 1995)
The "Report to an Academy" narrates a curious situation: an ape presents (or rather, performs) a report to an academy. What he presents is an autobiography. Like so much in Kafka, the "Report" is a parable about writing in general and about the writer's identity in particular. This essay attempts to address these issues through a close reading of Kafka's text against Blanchot's L'espace littéraire. Central to this endeavour is an analysis of the ape's use of the first-person pronoun as someone who fashions himself while, at the same time, presenting a theatrical autobiography featuring the self in question. My reading then moves on to analyze the act of writing as a negotiation of the passage between self and other, framed as it is by the theatrical context of Kafka's parable.
Keywords: Report to an Academy; Kafka; ape; presents; performs; autobiography; Report; parable; writing; writer& #x27; s identity; particular; Blanchot; L& #x27; espace littéraire; first-person pronoun; theatrical autobiography; self; narrator; negotiation; other